FERRO, Lígia; POVEDA, David (eds.) (2019), Arts and Ethnography in a contemporary world: From learning to social participation, London, Tufnell Press. - Varela, Pedro (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
.